Implementation of the PBL Model Integrated E-Module with Learning Differentiated to Promote Student’s Collaboration Skills - Yandari, Riri; Asrizal, Asrizal; Werina, Werina; Agusti, Hafiz Almahfuz (Universitas Negeri Padang, 2024)
Education is currently trying to make students able to master the skills of the 21st century. This study aims to determine the effect of applying the integrated e-module PBL model with differentiated learning on students' mastery of concepts and collaboration skills. The research design used in this research is classroom action research. The data collection instrument consists of two parts, namely the collaboration skills observation sheet and the writing test. Based on the results of data analysis, the results of increasing the average value of each indicator of collaboration skills in cycle I and cycle II due to the application of the integrated e-module PBL model with differentiated learning are: I1 = 13.19%, I2 = 8.33 %, I3 = 6.02%, I4 = 11.11%, I5 = 11.1%. While the increase in student knowledge aspect learning outcomes is 15.5%. Based on the research results, it is known that the application of the integrated e-module PBL model with differentiated learning can improve students' collaboration skills and mastery of concepts, which are skills needed in 21st century education.